Monitoring biofilm function in new and matured full-scale slow sand filters using flow cytometric histogram image comparison (CHIC). (1st July 2018) - Chan, Sandy; Pullerits, Kristjan; Riechelmann, Janine; Persson, Kenneth M.; Rådström, Peter; Paul, Catherine J.
Abstract: While slow sand filters (SSFs) have produced drinking water for more than a hundred years, understanding of their associated microbial communities is limited. In this study, bacteria in influent and effluent water from full-scale SSFs were explored using flow cytometry (FCM) with cytometric histogram image comparison (CHIC) analysis; and routine microbial counts for heterotrophs, total coliforms and Escherichia coli . To assess if FCM can monitor biofilm function, SSFs differing in age and sand composition were compared. FCM profiles from two established filters were indistinguishable. To examine biofilm in the deep sand bed, SSFs were monitored during a scraping event, when the top layer of sand and the schmutzdecke are removed to restore flow through the filter. The performance of an established SSF was stable: total organic carbon (TOC), pH, numbers of heterotrophs, coliforms, E. coli, and FCM bacterial profile were unaffected by scraping. However, the performance of two newly-built SSFs containing new and mixed sand was compromised: breakthrough of both microbial indicators and TOC occurred following scraping. The compromised performance of the new SSFs was reflected in distinct effluent bacterial communities; and, the presence of microbial indicators correlated to influent bacterial communities. This demonstrated that FCM can monitor SSF performance. Removal of the top layer of sand did not alter the effluent water from the established SSF, but did affect that of the SSFs containing new sand. This suggests that the impact of the surface biofilm on effluent water is greater when the deep sand bed biofilm is not established. Graphical abstract: Image Highlights: Removal of the schmutzdecke did not affect the function of established SSF. Use of preconditioned sand accelerated deep sand biofilm maturation in new SSF. FCM bacterial profiles correlated with the presence of microbial indicators. FCM is useful for process control of SSFs.